2013
DOI: 10.1186/1745-6215-14-144
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a dilemma-focused intervention for unipolar depression: study protocol for a multicenter randomized controlled trial

Abstract: BackgroundDepression is one of the more severe and serious health problems because of its morbidity, disabling effects and for its societal and economic burden. Despite the variety of existing pharmacological and psychological treatments, most of the cases evolve with only partial remission, relapse and recurrence.Cognitive models have contributed significantly to the understanding of unipolar depression and its psychological treatment. However, success is only partial and many authors affirm the need to impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 37 publications
2
41
0
1
Order By: Relevance
“…Ten participants were selected from a pool of 22 clients seen as part of the dilemma-focused intervention arm of an ongoing study of Feixas et al (2013. This is a randomized controlled clinical trial of psychotherapy for adults with depressive disorders that explore the relative efficacy of a dilemma-focused module intervention over standardized CBT.…”
Section: Methods Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten participants were selected from a pool of 22 clients seen as part of the dilemma-focused intervention arm of an ongoing study of Feixas et al (2013. This is a randomized controlled clinical trial of psychotherapy for adults with depressive disorders that explore the relative efficacy of a dilemma-focused module intervention over standardized CBT.…”
Section: Methods Participantsmentioning
confidence: 99%
“…In particular, a series of studies found that IDs were significantly more prevalent in depressive participants than in controls and that such cognitive conflicts were associated with the severity of patients' clinical complaints Feixas, Montesano, Erazo-Caicedo, Compañg, & Pucurull, 2014;. Consequently, a dilemma-focused intervention was devised to target IDs ) and is currently being tested for the treatment of depression in combination with standard CBT (Feixas et al, 2013). Preliminary analyses showed promising results for dilemma-focused therapy, which proved to be at least as effective as standard CBT in improving depressive symptoms and more suitable for helping clients resolving their IDs.…”
mentioning
confidence: 99%
“…For instance, psychological interventions could specifically target dilemmas insofar as they could constitute a focus of therapeutic work and allow individualizing the design of the treatment to fit patient subjective experience. It is noteworthy that although the concept of ID arose from a particular theoretical framework (personal construct theory), a dilemma-focused intervention could constitute an 'add-on' for a broad range of therapeutic models as it is being tested out in combination with CBT (Feixas et al, 2013). Thirdly, IDs can be detected by means of the RGT.…”
Section: Limitations and Clinical Implicationsmentioning
confidence: 99%
“…40 In addition, the efficacy of a dilemma-focused intervention in combination with cognitive behavioural therapy is being tested out for unipolar depression. 41 While the results of this study have clarified the role of implicative dilemmas and their content for dysthymic patients, there are some limitations that need to be considered. First of all, the lack of a matched control group restricted the generalizability of the results; likewise, the current comparison group was formed of a convenience sample with no control for undiagnosed disorders.…”
mentioning
confidence: 87%